2022
DOI: 10.1371/journal.pgen.1010374
|View full text |Cite
|
Sign up to set email alerts
|

FBB18 participates in preassembly of almost all axonemal dyneins independent of R2TP complex

Abstract: Assembly of dynein arms requires cytoplasmic processes which are mediated by dynein preassembly factors (DNAAFs). CFAP298, which is conserved in organisms with motile cilia, is required for assembly of dynein arms but with obscure mechanisms. Here, we show that FBB18, a Chlamydomonas homologue of CFAP298, localizes to the cytoplasm and functions in folding/stabilization of almost all axonemal dyneins at the early steps of dynein preassembly. Mutation of FBB18 causes no or short cilia accompanied with partial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Colocalization imaging in the Xenopus MCC cytoplasm shows that PF13/Ktu colocalizes with 5 different preassembly factors (ZMYND10, PIH1D3, SPAG1, LRRC6 and PF23/DYX1C1) and three chaperones (RUVBL1, RUVBL2, and HSP90) in DyNAPs [125]. In another study, co-immunoprecipitation and yeast two-hybrid assays identified that FBB18 interacts with these same three chaperones, as well as PF22, WDR92, ODA7 and PF23/DYX1C1, but not SPAG1, MOT48, RPAP3, or ZMYND10 [42,126]. PF13 and PF23 interact by immunoprecipitation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Colocalization imaging in the Xenopus MCC cytoplasm shows that PF13/Ktu colocalizes with 5 different preassembly factors (ZMYND10, PIH1D3, SPAG1, LRRC6 and PF23/DYX1C1) and three chaperones (RUVBL1, RUVBL2, and HSP90) in DyNAPs [125]. In another study, co-immunoprecipitation and yeast two-hybrid assays identified that FBB18 interacts with these same three chaperones, as well as PF22, WDR92, ODA7 and PF23/DYX1C1, but not SPAG1, MOT48, RPAP3, or ZMYND10 [42,126]. PF13 and PF23 interact by immunoprecipitation [44].…”
Section: Discussionmentioning
confidence: 99%